Coexistence of BRAF V600E and TERT Promoter Mutations in Low-grade Serous Carcinoma of Ovary Recurring as Carcinosarcoma in a Lymph Node: Report of a Case. (July 2019) - Tavallaee, Mahkam; Steiner, David F.; Zehnder, James L.; Folkins, Ann K.; Karam, Amer K.
Abstract : Low-grade serous carcinomas only rarely coexist with or progress to high-grade tumors. We present a case of low-grade serous carcinoma with transformation to carcinosarcoma on recurrence in the lymph node. Identical BRAF V600E and telomerase reverse transcriptase promoter mutations were identified in both the original and recurrent tumor. Given that telomerase reverse transcriptase promotor mutations are thought to play a role in progression of other tumor types, the function of telomerase reverse transcriptase mutations in BRAF mutated low-grade serous carcinoma deserves investigation.